Two-stage surgery for the treatment of nonmelanoma skin cancer of the face: Change of surgical strategy during COVID-19 pandemic. (December 2021) - Pagliuca, Giulio; Terenzi, Valentina; Martellucci, Salvatore; Clemenzi, Veronica; Stolfa, Andrea; Gallo, Andrea
Highlights: In case of high risk NMSC intra-operative assessment of resection margins is required. Intraoperative frozen sections permit to detect the presence of tumor in 72–91% of cases. In selected cases procedure currently replaced by more effective techniques could be applied.